Inside Back Cover: A Multi‐RNAi Microsponge Platform for Simultaneous Controlled Delivery of Multiple Small Interfering RNAs (Angew. Chem. Int. Ed. 10/2016). Issue 10 (4th February 2016) - Roh, Young Hoon; Deng, Jason Z.; Dreaden, Erik C.; Park, Jae Hyon; Yun, Dong Soo; Shopsowitz, Kevin E.; Hammond, Paula T.
Abstract : RNA interference (RNAi) has been intensively investigated as a powerful approach for therapeutic applications. In their Communication on page 3347 ff., P. T. Hammond et al. describe a modular platform for generating multiple polymeric RNAi molecules that self‐assemble and densely pack to form composite sponge‐like porous microstructures. The picture illustrates the precise ratiometric formation of microstructures from two polymeric RNAi molecules.